2022
DOI: 10.3390/cells11071148
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Prevents Liver Microthrombosis and Sepsis Induced Coagulopathy in a Rat Model of Endotoxemia

Abstract: Background: Endotoxemia causes endothelial dysfunction and microthrombosis, which are pathogenic mechanisms of coagulopathy and organ failure during sepsis. Simvastatin has potential anti-thrombotic effects on liver endothelial cells. We investigated the hemostatic changes induced by lipopolysaccharide (LPS) and explored the protective effects of simvastatin against liver vascular microthrombosis. Methods and results: We compared male Wistar rats exposed to LPS (5 mg/kg one i.p. dose) or saline in two experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…As Kume et al [27] reported that TM antigen and activity levels were significantly decreased in sinusoidal cells isolated from LPS-treated rats and recombinant TM protects against LPSinduced liver dysfunction, which indicates that decreased sinusoidal TM levels may result in liver dysfunction. And La Mura et al [28] also found that TM immunoreactivity was almost totally lost in endothelial cells 24 h after LPS injection, thus further confirming the involvement of the endothelium in the pathogenesis of liver damage induced by endotoxemia. Other researches also demonstrated that tumor necrosis factor [29] and other cytokines also aggravate vascular endothelial injury in liver cirrhosis, which can lead to the continuous increase of sTM level.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As Kume et al [27] reported that TM antigen and activity levels were significantly decreased in sinusoidal cells isolated from LPS-treated rats and recombinant TM protects against LPSinduced liver dysfunction, which indicates that decreased sinusoidal TM levels may result in liver dysfunction. And La Mura et al [28] also found that TM immunoreactivity was almost totally lost in endothelial cells 24 h after LPS injection, thus further confirming the involvement of the endothelium in the pathogenesis of liver damage induced by endotoxemia. Other researches also demonstrated that tumor necrosis factor [29] and other cytokines also aggravate vascular endothelial injury in liver cirrhosis, which can lead to the continuous increase of sTM level.…”
Section: Discussionmentioning
confidence: 79%
“…And La Mura et al . [ 28 ] also found that TM immunoreactivity was almost totally lost in endothelial cells 24 h after LPS injection, thus further confirming the involvement of the endothelium in the pathogenesis of liver damage induced by endotoxemia. Other researches also demonstrated that tumor necrosis factor [ 29 ] and other cytokines also aggravate vascular endothelial injury in liver cirrhosis, which can lead to the continuous increase of sTM level.…”
Section: Discussionmentioning
confidence: 79%
“…Many animal experiments have also proved the beneficial effect of statins on animal sepsis. [31][32][33] Therefore, statins may have a protective effect on sepsis and this may provide a new idea for the treatment of sepsis.…”
Section: Disscussionmentioning
confidence: 99%
“…In the setting of lipopolysaccharide-induced endotheliopathy in an animal model with increased microvascular thrombosis and vWF expression by liver ECs, statin treatment upregulates KLF2 and decreases thrombosis in the liver. [140] New research has built on this approach utilizing nanotechnology that enhances simvastatin delivery to LSECs to augment KLF2. [141] This field is developing, and given that the nanotechnology in this study relied on targeting the mannose receptor on LSECs with mannan-containing nanoparticles, which while demonstrating preferential LSEC uptake lack total specificity, [142] more specialized technology should be used for further precision therapy.…”
Section: Fibrosis and Mechanosensingmentioning
confidence: 99%
“…Recent studies demonstrated that statins ameliorate prothrombotic endotheliopathy in the liver as well. In the setting of lipopolysaccharide-induced endotheliopathy in an animal model with increased microvascular thrombosis and vWF expression by liver ECs, statin treatment upregulates KLF2 and decreases thrombosis in the liver 140 . New research has built on this approach utilizing nanotechnology that enhances simvastatin delivery to LSECs to augment KLF2 141 .…”
Section: Introductionmentioning
confidence: 99%